PENGARUH PENGELOLAAN SARANA DAN PRASARANA TERHADAP KINERJA PEGAWAI DI DINAS KESEHATAN KABUPATEN KULON PROGO DIY - Agung Hartadi; Nurhadi Nugroho (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2022)
This research examines the effect of the management of facilities and infrastructure on the performance of the Health Service of Kulon Progo Regency, DIY. Based on the t-test carried out, it can be seen that the t-count value is 3.763 > t table which is 2.40835 with a probability value of 0.000 <0.05, then the management variable facilities and infrastructure have a partial effect on employee performance, this proves that the hypothesis proposed by the researcher is accepted. The calculation of R Square that is done can be seen that the value of R Square is 0.228 or 22.8%. The magnitude of the influence of the variable management of facilities and infrastructure on employee performance is 22.8%. The correlation test carried out can be seen that the correlation number between the management of facilities and infrastructure and employee performance is 0.477. This means that the relationship between the two variables is positively correlated (unidirectional). Judging from the probability number (sig) of 0.000 <0.05, the management of infrastructure and employee performance has a significant relationship.